An electrophoretic study of fetal mouse brain proteins after in vivo exposure to phenytoin and disulfiram - Heiberg, Ludvig (Division of Clinical Pharmacology, 2018)
Although there have been two-dimensional electrophoretic studies on fetal brain tissue (for instance, Yoshida and Takahashi, 1980), the emphasis in most of this work has been on developmental changes in protein expression, and not on the effects that drugs have on fetal brain protein complement. Klose and co-workers (1977) did an early study using two-dimensional gel electrophoresis to determine the effects of various teratogens on whole embryos. No protein changes were found and that line of research was not continued. In this study two-dimensional gel electrophoresis is extensively used, in the belief that the usefulness of this technique to experimental teratology has not been fully evaluated. It is reasonable to suppose that a central nervous system teratogen administered during critical periods of susceptibility will led to perturbations of orderly brain development, and that these perturbations will be reflected as changes to the protein complement. The total brain protein complement of mice that have been exposed to drugs in utero will therefore be analysed, in the hope that any inductions or deletions of proteins as a result of drug exposure may provide a clue to the molecular events underlying drug injury to the fetus.